Sistem Monitoring Level Air dan Volume Air Menggunakan Sensor Ultrasonic Berbasis Blynk (IoT) - Putri Ayu Dina; Nadila Hardiyanty; Mutiara Isya Meliana; Resti Dwi Artika; Susilawati, M.Si (Peneliti.net, 2026)
This study presents the design and implementation of a real-time water level and volume monitoring system for water towers, aimed at preventing water shortages and ensuring efficient water management. The system is built on the Internet of Things (IoT) framework, utilizing the Blynk platform to enable remote monitoring. Water height is measured using an HC-SR04 ultrasonic sensor, while an ESP32 microcontroller processes the collected data. The water level information is displayed both locally on a 16x2 I2C LCD and remotely via the Blynk application, allowing users to monitor water status anytime and anywhere. Furthermore, the system is equipped with a notification feature that alerts users when the water level approaches the minimum threshold, enhancing proactive management. The proposed system demonstrates a simple, cost-effective, and reliable solution for real-time water monitoring, providing both convenience and operational efficiency in water resource management.